2000
DOI: 10.1128/iai.68.7.3983-3989.2000
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Virulence Genes and Clonality in Escherichia coli Strains That Cause Bacteremia in Cancer Patients

Abstract: Phenotypic analysis of Escherichia coli strains causing bacteremia in cancer patients suggests that they possess specific virulence properties. To investigate this hypothesis, we compared the frequency of the virulence-related genes cnf1, cnf2, papC, hlyC, and iut in 155 E. coli strains isolated from hospitalized cancer patients with epidemiologically unrelated cases of bacteremia to their frequency in 70 E. coli strains isolated from the feces of healthy unrelated volunteers. Of the blood isolates, 24, 37, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 63 publications
4
39
0
Order By: Relevance
“…The strains from Mali harboured fewer virulence factors than did the Croatian (U-test, P l 0n005) and French (U-test, P l 0n0039) isolates, as only one Malian strain (B2 group) possessed two virulence factors versus 23 strains in Croatia and 19 strains in France. These data are consistent with most studies on the frequency of virulence factors in strains from healthy human stools (Minshew et al, 1978 ;Hagberg et al, 1981 ;Goullet & Picard, 1986b ;Opal et al, 1990 ;Siitonen, 1992 ;Hilali et al, 2000). The frequent occurrence of commensal strains with virulence determinants reported by Mu$ hldorfer et al (1996) may be due to a local epidemiological bias, as no such prevalence was found by these workers in Peru (Hacker et al, 1983).…”
Section: Distribution Of Extraintestinal Virulence Genes Among Human supporting
confidence: 81%
See 1 more Smart Citation
“…The strains from Mali harboured fewer virulence factors than did the Croatian (U-test, P l 0n005) and French (U-test, P l 0n0039) isolates, as only one Malian strain (B2 group) possessed two virulence factors versus 23 strains in Croatia and 19 strains in France. These data are consistent with most studies on the frequency of virulence factors in strains from healthy human stools (Minshew et al, 1978 ;Hagberg et al, 1981 ;Goullet & Picard, 1986b ;Opal et al, 1990 ;Siitonen, 1992 ;Hilali et al, 2000). The frequent occurrence of commensal strains with virulence determinants reported by Mu$ hldorfer et al (1996) may be due to a local epidemiological bias, as no such prevalence was found by these workers in Peru (Hacker et al, 1983).…”
Section: Distribution Of Extraintestinal Virulence Genes Among Human supporting
confidence: 81%
“…This absence of difference was also found for each virulence gene (Table 3). In addition, confirming that the strains of phylogenetic group B2 are more frequent among extraintestinal pathogenic strains (40-72 %) than among commensal strains (9-11 %) (Goullet & Picard, 1986b ;Johnson et al, 1991 ;Bingen et al, 1998 ;Picard et al, 1999 ;Hilali et al, 2000 ; this work), our homogeneous dataset also increases our understanding of the emergence of virulence in human extraintestinal infections. The smaller number of virulence determinants in commensal strains of phylogenetic groups A, B1 and D than in the corresponding pathogenic strains is consistent with the hypothesis (Bingen et al, 1998 ;Lecointre et al, 1998 ;Picard et al, 1999) that these strains acquire virulence factors by horizontal transfer, enabling them to become virulent and to invade immunocompetent hosts (Picard & Goullet, 1988) from the host's intestinal reservoir.…”
Section: Comparison Of Human Commensal Strain Data With Data Obtainedsupporting
confidence: 63%
“…Bloodstream infections in which the bacteria are derived from the intestinal flora by bacterial translocation are common in patients with cancer. Preliminary results showed that the afa-8 operon is found in CNF1-producing strains associated with this type of bacteremia (22,38,42). Therefore, afa-8 is probably involved in the development of extraintestinal infections associated with primary colonization of the intestine.…”
mentioning
confidence: 99%
“…The virulence potential of ExPEC is determined largely by the presence of specialized VFs, which can be located on large plasmids or on the chromosomes of pathogenic strains. Recognized VFs of ExPEC, which are infrequent among commensal strains, include adhesins (P, S, and F1C fimbriae and Afa-related adhesins), toxins (hemolysin and cytotoxic-necrotizing factor 1), siderophores (aerobactin and yersiniabactin), capsules (K1, K5, and K12), invasins (Ibe10 and afaD genes), and factors contributing to serum resistance (5,22,28,55). Most VF genes are located on PAIs, which are large segments of chromosomal DNA inserted within or near tRNA genes.…”
mentioning
confidence: 99%
“…[1] The deadly E.coli outbreak killed persons and spread across Europe in May 2011. Multidrugresistant E. coli (MDR-ECO) strains have increased with the application of broad-spectrum antibiotics.…”
Section: Introductionmentioning
confidence: 99%